2014
DOI: 10.3892/mmr.2014.3003
|View full text |Cite
|
Sign up to set email alerts
|

Multi-dose parecoxib provides an immunoprotective effect by balancing T helper 1 (Th1), Th2, Th17 and regulatory T cytokines following laparoscopy in patients with cervical cancer

Abstract: Analgesic treatment with anti‑inflammatory drugs may aid the prevention of postoperative pain and the attenuation of the postoperative immune inflammatory response. The current study presents a randomized, double‑blind controlled study, which was performed to investigate the levels of Th1, Th2, Th17 and Treg cytokines, including interleukin (IL)‑2, interferon (IFN)‑γ, IL‑4, IL‑10, IL‑17, IL‑23 and transforming growth factor (TGF)‑β in the peripheral blood of patients with cervical cancer following laparoscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The tumor classification of the patients in the present study was consistent with the literature reported previously (22). Accumulating evidence has altered the traditional paradigm of Th1/Th2 cytokine classification to include two novel subsets of CD4 + T cells, Th17 and Treg cells, which are characterized by their distinct cytokine profiles (34)(35)(36). Th17 and Treg cells predominantly produce IL-17 and TGFβ family cytokines, respectively (37).…”
Section: Discussionsupporting
confidence: 80%
“…The tumor classification of the patients in the present study was consistent with the literature reported previously (22). Accumulating evidence has altered the traditional paradigm of Th1/Th2 cytokine classification to include two novel subsets of CD4 + T cells, Th17 and Treg cells, which are characterized by their distinct cytokine profiles (34)(35)(36). Th17 and Treg cells predominantly produce IL-17 and TGFβ family cytokines, respectively (37).…”
Section: Discussionsupporting
confidence: 80%
“…Th1 and Th2 may be involved in the pathogenesis and growth of cervical cancer. Th1 may be the target of predicting chemotherapy response of advanced cervical cancer [47][48][49][50] , while other pathways are classical signal pathways related to cancer. Immune cytokines play an important role in cervical lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Th1, Th2, Th17 and Tregs produce positive or negative effects in the maintenance of normal immune function by secreting various cytokines: interleukin-2 (IL-2) and interferon-γ (IFN-γ), the principal cytokines delivered by Th1cells, IL-12, a key cytokine involved in inducing and maintaining Th1cells and the IFN-γ responses, and IL-10, a potent modulator of cell-mediated immune responses secreted by Th2. 26 IL-17 is a recently identified pro-inflammatory cytokine secreted by Th17 cells. According to a previous report, IL-17 promotes angiogenesis and cell proliferation and invasion in CC.…”
Section: Cervical Cancer and The Immune Landscapementioning
confidence: 99%